Effects of NDRG2 Overexpression on Metastatic Behaviors of HCT116 Colorectal Cancer Cell Line - Ali Golestan; Abbas Ghaderi; Zahra Mojtahedi (Tabriz University of Medical Sciences, 2017)
Purpose: N-myc downstream-regulated gene 2 (NDRG2) is frequently down-regulated in cancer, and plays an important role in the control of tumor growth and metastasis. Its manipulation has been suggested as a therapy in cancer. Here, we examined the outcome of NDRG2 overexpression on proliferation, invasion, migration and MMP activity of HCT116 colorectal cancer cell line. Methods: The HCT116 cell line (human colorectal cancer) was transfected with pCMV6-AC-GFP-NDRG2. 2,5diphenyltetrazolium bromide (MTT) assay was used to detect cell proliferation. The invasion and migration of the transfected cells were examined through transwell chambers while the MMP-9 activity was detected by the ability of the cells to digest gelatin. Results: Overexpression of NDRG2 by stable NDRG2 transfection decreased cell proliferation, migration and invasion ability, along with decreasing MMP-9 activity. Conclusion: Our data indicate that NDRG2 overexpression can suppress several aspect of tumorigenesis. Further investigations are necessitated to verify if NDRG2 molecule can be a therapeutic target in colorectal cancer.